Kh. Hasyim Muzadi’s Language Politeness Strategies in Responding The Different Perspective Between Nahdlatul Ulama and Muhammadiyah: a Sociopragmatic Study - Muta'allim (MUSLIM HERITAGE, 2025)
This study highlights the concept of religious moderation as a strategic approach to mitigating conflicts that arise from differing religious viewpoints. The main objective of this research is to identify and explain the politeness strategies in language used by KH. Hasyim Muzadi (KHHM) in addressing national issues, using a socio-pragmatic approach. This study employs a qualitative descriptive method. The data analyzed consists of utterances containing language politeness strategies, with the data sources being speeches and statements made by KHHM that were uploaded to YouTube gontortv. Data collection was conducted by searching various social media platforms, online news sources, and related manuscripts. Once relevant materials were found, the researcher downloaded and watched KHHM's speech videos, then transcribed all utterances containing elements of politeness in language. After gathering the data, the researcher classified and validated the findings based on their relevance to the research questions. The results of the study show that: (1) the concept of religious moderation is effective in reducing the potential for religious conflict in Indonesia; (2) language politeness strategies are proven to be effective in addressing differing viewpoints, particularly between Nahdlatul Ulama and Muhammadiyah, and in encouraging mutual respect among Muslims; (3) the implementation of these strategies is influenced by several factors, such as the interlocutor’s characteristics, the social situation, the topic of conversation, the purpose of communication, and its impact on social relations; and (4) KHHM’s application of language politeness has a positive impact in fostering humane communication and harmonious social relationships, allowing communities to live together in safety, peace, and harmony.   Abstrak Penelitian ini mengangkat konsep moderasi beragama sebagai pendekatan strategis dalam meredam konflik yang timbul akibat perbedaan perspektif keagamaan. Tujuan utama penelitian ini adalah untuk mengidentifikasi dan menjelaskan strategi kesantunan berbahasa KH. Hasym Muzadi (KHHM) dalam merespons persoalan-persoalan kebangsaan, dengan menggunakan pendekatan sosio-pragmatik. Penelitian ini menggunakan pendekatan deskriptif kualitatif. Data yang dianalisis berupa tuturan yang mengandung strategi kesantunan berbahasa, sedangkan sumber data diperoleh dari pidato dan pernyataan KH. Hasyim Muzadi (KHHM) yang diunggah di platform YouTube gontortv. Pengumpulan data dilakukan dengan menelusuri berbagai media sosial, berita daring, dan naskah terkait. Setelah menemukan materi yang relevan, peneliti mengunduh dan menonton video pidato KHHM, kemudian mencatat seluruh tuturan yang mengandung unsur kesantunan berbahasa. Setelah data terkumpul, peneliti melakukan klasifikasi dan validasi berdasarkan kesesuaiannya dengan rumusan masalah. Hasil penelitian menunjukkan bahwa (1) konsep moderasi beragama efektif dalam mereduksi potensi konflik keagamaan di Indonesia; (2) strategi kesantunan berbahasa terbukti ampuh dalam merespons perbedaan pandangan, khususnya antara Nahdlatul Ulama (NU) dan Muhammadiyah (MD), serta mampu mengajak umat Islam untuk saling menghargai perbedaan; (3) penerapan strategi tersebut dipengaruhi oleh beberapa faktor, seperti karakteristik lawan tutur, situasi sosial, topik pembicaraan, tujuan komunikasi, serta dampaknya terhadap relasi sosial; dan (4) penerapan kesantunan berbahasa KHHM berdampak positif dalam membentuk komunikasi yang humanis dan hubungan sosial yang harmonis, sehingga masyarakat dapat hidup berdampingan secara aman, damai, dan tenteram. Keywords: KH. Hasyim Muzadi; Language Politeness Strategies; Concept of Religious Moderation